Building brand, building value: The impact of customer-based brand equity on airline ticket premium pricing - Santos, C. (2024)
This study examines the impact of Customer-based Brand Equity (CBBE) on passengers’ Willingness to Pay Premium (WPP) for airline tickets, comparing low-cost and flag airlines. The research is prompted by the competitive nature of the industry and the need to comprehend passenger preferences, focusing on brand image, brand awareness, and service attributes as key variables influencing CBBE. The survey data collected from 489 recent travelers were analyzed through Partial Least Squares Structural Equation Modelling (PLS-SEM) and Multigroup Analysis (MGA), generating two quantitative analyses: first, the model was analyzed for airlines in general, and second, a multi-group analysis was performed to understand how the model behaves through price tiers. The findings indicate the significant influence of the chosen variables on both CBBE and WPP. A distinguishing factor lies in the differentiation between low-cost and flag airlines, revealing differing impacts on CBBE and WPP. This research contributes to the branding literature by expanding CBBE’s application to services, especially in the airline sector. It also builds on existing knowledge of WPP’s importance in service industries. Segmenting airline price tiers offers actionable insights for management strategies. In conclusion, this study augments the knowledge of CBBE, providing valuable managerial implications, guiding brand-tailored strategies to increase passengers’ willingness to pay premium.